PATHOGENESIS AND PATHOGENETICALLY SUBSTANTIATED THERAPY OF CHRONIC ENDOMETRITIS (сlinical lecture) - I. S. Sidorova; I. O. Makarov; A. L. Unanyan; R. S. Vlasov; D. V. Karpov (IRBIS LLC, 2016)
Chronic endometritis (CE) - a common disease with no unified concept of pathogenesis, characterized by undulating and ever-progressive pathological process. Important pathogenic factors contributing to the development of CE, is immune deficiency and violation of endometrium angioarchitectonics. Currently has been widely discussed question of the pro- and antioxidant systems imbalance role in the pathogenesis of HE. From these positions, it is obvious that the stimulation of natural antioxidant systems, introduction of exogenous antioxidants - one of the essential moments in the treatment of CE. Actovegin is a one of the modern drugs which is best meets the requirements of CE pathogenic-based therapy and has an impact on the above links of pathogenesis. Actovegin contains components with high biological activity: amino acids, oligopeptides, nucleosides, oligosaccharides and glycolipides, enzymes, electrolytes, and a number of important macro- and micronutrients. Exacerbation of already existing chronic inflammation often occurs after an abortion and therapeutic surgical procedures. Therefore, an important measure to prevent the exacerbation of chronic endometritis, an essential part of the treatment of post-abortion or postpartum CE, treatment and diagnostic curettage is the rehabilitation of structural and functional state of the endometrium with the use of Actovegin.